(untitled) (diségno, 2018)
From ancient times to the present day, architects and engineers have tried to express their designs in materials that allow them to transfer the creations from their mind to the tangible world, bringing them to life through models showing a future or hypothetical constructed reality. There have been more than 5,000 years between the first intuitive representations and the current immersive virtual reality prototypes, over which time the search for a universal graphic representation model has been a constant and three-dimensionality has always played an essential role [1].